2016
DOI: 10.1038/npjbiofilms.2015.29
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria differently deploy type-IV pili on surfaces to adapt to nutrient availability

Abstract: The structure of bacterial biofilms depends on environmental conditions, such as availability of nutrients, during biofilm formation. In turn, variations in biofilm structure in part reflect differences in bacterial motility during early biofilm formation. Pseudomonas aeruginosa deprived of nutrients remain dispersed on a surface, whereas cells supplemented with additional nutrients cluster and form microcolonies. At the single-cell scale, how bacteria modify their motility to favour distinct life cycle outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(67 citation statements)
references
References 64 publications
(70 reference statements)
5
47
0
2
Order By: Relevance
“…In particular, it has been experimentally shown that the emergence of bacterial antibiotic resistance was accelerated in heterogeneous microenvironments [66]. Further, various strains of bacteria were shown to possess the capability to actively form niches to adapt to different environments, such as changes in nutrient availability [45]. It is also worth noting that the concept of persister cells was first described in the context of bacterial infections in which a small number of antibiotic-resistant mutants survived in a dormant non-dividing state [4,36].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it has been experimentally shown that the emergence of bacterial antibiotic resistance was accelerated in heterogeneous microenvironments [66]. Further, various strains of bacteria were shown to possess the capability to actively form niches to adapt to different environments, such as changes in nutrient availability [45]. It is also worth noting that the concept of persister cells was first described in the context of bacterial infections in which a small number of antibiotic-resistant mutants survived in a dormant non-dividing state [4,36].…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial motility would be affected by the number of pili and how those pili distribute at the bacteria poles 2,17 . Therefore, the present model is employed to understand how the number of pili and the distribution angle ( α ) influence twitching characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…Twitching motility could depend on many factors including surface properties, pili arrangement on bacterial surface, and environmental conditions such as oxygen concentration and fluid flow rate 16 . For example, when pili emanate only at the poles of bacteria (e.g., Pseudomonas aeruginosa ), the bacteria will have persistent motion 17,18 . But, if pili are all around the cell body (e.g., Neisseria gonorrhoeae ), the bacteria will have trapped or diffusive motion due to the tug of war mechanism 19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The next stages involve the clumping of cells into microcolonies and growth into a biofilm structure, which can be flat or mushroom-like (Figure 1). The shape of the colony is influenced by the growth and rearrangement of cells through pili-mediated gliding, depending on the available nutrients [5,6]. In the final stage of biofilm growth some motile cells are shed from the biofilm, where they are then able to colonize other surfaces in a new location.…”
Section: Biofilms -Bacterial Simplicity With Tissue-like Complexitymentioning
confidence: 99%